Instagram Content Marketing Improvement Design Of Indihomegamer.Id Using Swot Analysis And Qspm - Vietra Shauma Ranabilla; Agus Achmad Suhendra; Ima Normalia Kusmayanti (eProceedings of Engineering, 2022)
AbstractPandemic COVID-19 has encouraged people to spend more time at home, leading to an increase in the gaming industry in Indonesia. One of the companies that was affected by this increase is PT Melon Indonesia in its gaming products, one of them is IndiHome Paket Gamer. In doing its marketing activity, IndiHome Paket Gamer uses Instagram to promote their product to the public. However, the performance of its Instagram account is still considered lacking because the percentage of its engagement rate is below average and still lower compared to other competitor accounts with the same theme. Therefore, this research is conducted to analyze the strengths, weaknesses, opportunities, and threats of PT Melon Indonesia in managing its IndiHome Paket Gamer Instagram to design the content marketing strategy that is best and suitable for improving their Instagram account performance using SWOT analysis and QSPM. This design process resulted seven strategies formulated and the best content marketing strategy of IndiHome Paket Gamer Instagram is to carry out modification of content planning based on the result of reviews and research from Instagram accounts with the same theme.Keywords: Content Marketing Strategy, Internal and External Analysis, IFE EFE Matrix, IE Matrix, SWOT Matrix, QSPM